Giant pedunculated oesophageal liposarcomas: A review of literature and resection techniques. (2019) - Ng, Y. Annalisa; Lee, June; Zheng, X.J.; Nagaputra, J.C.; Tan, S.H.; Wong, S.A.
Highlights: Giant oesophageal liposarcomas, a rare but important cause of oesophageal tumours. A review of the current literature focusing on resection techniques. Shift in the treatment paradigm in recent years to endoscopic resection techniques. Decision on type of resection technique depends on tumour characteristics and location. Abstract: Introduction and presentation of case: Liposarcomas are rare causes of oesophageal tumours, accounting for <1% of tumours. We present a case of a dedifferentiated oesophageal liposarcoma arising from a giant fibrovascular polyp for which resection was performed via a left cervical oesophagostomy with transgastric retrieval of tumour. We also review the existing literature focusing on discussion of resection techniques. Discussion: To date, 62 cases of oesophageal liposarcoma have been reported in the literature. They usually occur in males (74.2%), with a median age of 66 years (range 38–84 years). Such tumours present most commonly with dysphagia (69.4%); usually arise from the cervical oesophagus (79%), and are well-differentiated. Treatment options include surgery and recently, endoscopic resection techniques such as submucosal dissection (ESD). Conclusion: Giant oesophageal liposarcomas are very rare tumours. Such tumours are usually polypoid, arising from a pedicle. As such, resection techniques have shifted away from oesophagectomy to less invasive means such as endoscopic resection or oesophagostomy. Decision on type of resection technique depends on tumour characteristics and location; with the guiding principle being resection with clear margins in order to prevent local recurrence.